IBM Supply Chain Transformation - Smith, Galen (IBM Redbooks, 2021)
In the midst of global disruptions, every element of IBM® Supply Chain has been affected. The IBM cognitive supply chain is positioned to win the future by using the exponential technologies that are inherent to our supply chains, and with flexibility, resiliency, and end-to-end visibility. The constant commitment of IBM to building smarter supply chains over the past decade has primed IBM to quickly and effectively navigate these disruptions and course-correct by using cognitive innovation. As a result, IBM Supply Chain teams were able to deliver exceptional outcomes without client disruption. In addition, this widespread impact inspired numerous new solutions that include exponential technologies that better prepare IBM for future disruptions in constantly changing markets.